SP-closedness in L-fuzzy topological spaces - Bai Shi-Zhong (International Journal of Mathematics and Mathematical Sciences)
We introduce and study SP-closedness in L-fuzzy topological spaces, where L is a fuzzy lattice. SP-closedness is defined for arbitrary L-fuzzy subsets.